2011
DOI: 10.1016/j.yhbeh.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for progesterone's protection against lordosis-inhibiting effects of restraint

Abstract: Progestins and antiprogestins are widely used therapeutic agents in humans. In many cases, these are indicated for the treatment of reproductive activites. However, progesterone has widespread physiological effects including a reduction of the response to stress. We have reported that 5 min of restraint reduced lordosis behavior of ovariectomized rats hormonally primed with estradiol benzoate. When ovariectomized rats received both estradiol benzoate and progesterone priming, restraint had minimal effects on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 59 publications
7
33
0
2
Order By: Relevance
“…In previous experiments [44, 45, 55], we have reported that a mild 5 min restraint reduced lordosis behavior in ovariectomized rats that were hormonally primed with 10 µg estradiol benzoate but not in naturally cycling rats or in ovariectomized rats primed with estradiol benzoate and progesterone. A role for intracellular progesterone receptors in this resistance to the lordosis-inhibiting effects of the restraint was suggested by the ability of both RU486 and of the more selective progesterone receptor antagonist, CDB4124, to block effects of progesterone [44, 56]. In the current experiment, in all treatments with RU486, lordosis behavior was reduced by restraint.…”
Section: 0 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous experiments [44, 45, 55], we have reported that a mild 5 min restraint reduced lordosis behavior in ovariectomized rats that were hormonally primed with 10 µg estradiol benzoate but not in naturally cycling rats or in ovariectomized rats primed with estradiol benzoate and progesterone. A role for intracellular progesterone receptors in this resistance to the lordosis-inhibiting effects of the restraint was suggested by the ability of both RU486 and of the more selective progesterone receptor antagonist, CDB4124, to block effects of progesterone [44, 56]. In the current experiment, in all treatments with RU486, lordosis behavior was reduced by restraint.…”
Section: 0 Discussionmentioning
confidence: 99%
“…For example, ovariectomized Fischer female rats may show high sensitivity because a single injection of 10 µg estradiol benzoate to naive ovariectomized females elicits near maximal lordosis behavior (but not proceptivity) in a majority of females [44, 45] while comparable treatment is not reported to elicit high lordosis responding in Sprague Dawley or Wistar females [20, 46]. …”
Section: 0 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When ovariectomized Fischer rats are injected with 10 μg EB, the emergence of lordosis behavior (but not proceptivity) can be as high as observed in rats given EB and 500 μg progesterone, but when these 10 μg EB treated rats are given a brief 5 min restraint experience, lordosis behavior is rapidly reduced. The addition of progesterone completely prevents this restraint-induced decline (Hassell et al, 2011; Miryala et al, 2011; White and Uphouse, 2004) and the antiprogestins, RU486 or CDB4124, reduce progesterone’s ability to attenuate the effect of restraint (Hassell et al, 2011; Uphouse and Hiegel, 2013). However, when rats were given 4 consecutive weeks of treatment with 10 μg EB, the repeated treatment with estradiol benzoate was as effective as the addition of progesterone in reducing the lordosis-inhibiting effect of a 5 min restraint stress (Uphouse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%